Hospital Safety Box Monitoring: Building Brand Trust in Healthcare Business During Covid -19 Wave - Johansyah, Muhamad Deni; Purnama, Susan (International Journal of Global Operations Research, 2021)
The health business is adjusting to a new reality where bargaining power has shifted to consumers. Consumers are now playing a key role in the commercialization process, making them important stakeholders to fulfill their needs. Health business reforms have convinced consumers to give protection a greater priority than ever since the COVID-19 pandemic escalated around the world. Health care businesses in Indonesia are no exception, should increase their brand trust, because of the huge responsibility to protect consumers from the prevention of COVID-19, and brand trust also gives added value to the hospital's own brand. A brand with the right value proposition can "prove" the true value of its product or service to patients in the minds of consumers, one of which is from medical waste management. Hospital waste is usually a contagious and toxic chemical that can affect human health and environmental impacts if not treated properly. Medical waste including sharp objects, infectious waste, pharmaceutical waste, and other waste is mostly generated in health facilities such as health centers and hospitals. such as intravenous lines, syringes, gloves, which after use must be handled and destroyed in such a way that they do not fall into the hands of the public or even injure medical personnel. The Smart Waste concept is here to answer the challenges of trust in hospital brands in Indonesia, especially in the city of Bandung, increasing the sense of security of consumers is the main goal of this concept where hospital safety boxes work together with sensors and microcontrollers, disposal of syringes can be done more intelligently. , safe and the risk of medical personnel punctured by infected needle waste can be reduced.